Confronting Tigecycline-Resistant Acinetobacter baumannii via Immunization Against Conserved Resistance Determinants - Chiang, Ming-Hsien; Yang, Ya-Sung; Sun, Jun-Ren; Wang, Yung-Chih; Kuo, Shu-Chen; Lee, Yi-Tzu; Chuang, Yi-Ping; Chen, Te-Li (Frontiers in Microbiology, 2020)
Antimicrobial-resistant (AMR) bacterial infections, including those caused by Acinetobacter baumannii, have emerged as a clinical crisis worldwide. Immunization with AMR determinants has been suggested as a novel approach to combat AMR bacteria, but has not been validated. The present study targeted tigecycline (TGC) resistance determinants in A. baumannii to test the feasibility of this approach. Using bioinformatic tools, four candidates, AdeA, AdeI, AdeK, and TolC, belonging to the resistance-nodulation-division (RND) efflux pump were identified as highly conserved and exposed antigens from 15 A. baumannii genomes. Antisera generated from recombinant proteins showed the capability to reserve Hoechst 33342, a substrate of the efflux pump, in bacterial cells. The rTolC antisera had the highest complement-dependent killing and opsonophagocytosis effect compared to the sera from phosphate-buffered saline immunized mice. Among the antisera, anti-rAdeK-specific antisera decreased the minimal inhibitory concentration of TGC in 26.7% of the tested isolates. Immunization with rAdeK significantly potentiated TGC efficacy in treating TGC-resistant A. baumannii pneumonia in the murine model. The bacterial load (7.5 × 105 vs. 3.8 × 107, p < 0.01) and neutrophil infiltration in the peri-bronchial vasculature region of immunized mice was significantly lower compared to the PBS-immunized mice when TGC was administrated concomitantly. Collectively, these results suggest that active immunization against resistance determinants might be a feasible approach to combat multidrug-resistant pathogens in high risk population.